2022
DOI: 10.1186/s12913-022-07847-0
|View full text |Cite
|
Sign up to set email alerts
|

Health system impacts of SARS-CoV − 2 variants of concern: a rapid review

Abstract: Background As of November 25th 2021, four SARS-CoV − 2 variants of concern (VOC: Alpha (B.1.1.7), Beta (B.1.351), Gamma (P.1), and Delta (B.1.617.2)) have been detected. Variable degrees of increased transmissibility of the VOC have been documented, with potential implications for hospital and health system capacity and control measures. This rapid review aimed to provide a synthesis of evidence related to health system responses to the emergence of VOC worldwide. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 80 publications
0
11
0
Order By: Relevance
“…Reports have shown that variants presented variable transmission patterns, virulence, severity of disease symptoms, and compromised vaccine protection. 56 57 58 59 In this study, we analysed the heterogeneity between the dominating SARS-CoV-2 variants and long term health outcomes after mild infection. Comparison of the wild-type strain and the alpha variant up to a year after infection showed no significant differences in health outcomes, and variants showed similarity in both early and late time periods.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reports have shown that variants presented variable transmission patterns, virulence, severity of disease symptoms, and compromised vaccine protection. 56 57 58 59 In this study, we analysed the heterogeneity between the dominating SARS-CoV-2 variants and long term health outcomes after mild infection. Comparison of the wild-type strain and the alpha variant up to a year after infection showed no significant differences in health outcomes, and variants showed similarity in both early and late time periods.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, to quantify the risk for long term health outcomes associated with mild SARS-CoV-2 infection in unvaccinated people, we analysed a sub-cohort of unvaccinated SARS-CoV-2 infected and non-infected pairs during wild-type virus and alpha variant periods and compared all reported covid-19 outcomes between pairs (we did not include the delta variant owing to insufficient follow-up). We categorised age into six age groups: three children's subgroups (0-4, 5-11, and 12-18 years) and three adults' subgroups (41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58)(59)(60), and >60) (supplementary table S2a). The follow-up period was from the second to 12th month after the PCR test, to target outcomes related to covid-19 after the acute period (first month).…”
Section: Methodsmentioning
confidence: 99%
“…Changes in the dominant SARS-CoV-2 variants of concern over time meant that blood operators needed to review policies focussed on enhancing staff safety and reducing transmission in the workplace [ 36 , 37 ] ( Table 1 ). We also spent considerable time understanding the safety of vaccine and the importance of vaccination in reducing the burden of disease in society [ 38 , 39 , 40 ].…”
Section: Lessons Learnedmentioning
confidence: 99%
“…These studies have resulted in the implementation of the preventive anti-inflammatory remedies and pathogenetic therapies in SARS-CoV-2 patients, such as hydroxychloroquine, chloroquine, azithromycin, ivermectin, colchicine, thalidomide and glucocorticoids methylprednisolone and dexamethasone, the monoclonal antibody tocilizumab, convalescent plasma interferons, and intravenous immunoglobulin therapy ( 7 9 ). However, these types of medicine are often unaffordable in low-income countries ( 10 ), which become a natural reservoir of the virus and a prerequisite of the appearance of new mutations ( 11 ).…”
Section: Introductionmentioning
confidence: 99%